Sexting Types and Motives Detected among Slovak Adolescents - Hollá, Katarína (European Journal of Mental Health, 2020)
The present study maps different types of adolescent sexting in the Slovak Republic, i.e. primary and secondary sexting, as well as self- and peer-sexting. Our research has been focused on the investigation and comparison of motives that make the adolescents of different ages and genders decide for voluntary, forced, primary, secondary, self- or peer-sexting. The research sample included 790 Slovak adolescents aged 12–18, of which 376 were boys (47.6%) and 414 were girls (52.4%). The gender-based comparison provided us with statistically significant differences in pursuing various types of sexting. The most frequent form of sexting is peer sexting. In terms of motivation, the research shows that most adolescents use individual sexting forms to seek attention or entertain themselves. Secondary sexting (as the most dangerous form of this behavior) is most often driven by entertainment, retaliation, revenge and jealousy. All these motives were also statistically more significant for male respondents.